ONTOGENY OF DREVERMANNIA AND THE ORIGIN OF BLINDNESS IN LATE DEVONIAN PROETOID TRILOBITES - Lerosey-aubril R. (My University, 2006)
Numerous silicified and calcareous sclerites of various sizes, recovered from the latest Famennian of Thuringia (Germany), allow the description of the first complete growth series of a blind proetoid trilobite: Drevermannia richteri. In addition, the partial ontogenetic development of Drevermannia antecurvata sp. nov. and undetermined species, Drevermannia sp. 1, are described. The proetoid anaprotaspides, associated with D. richteri, illustrate that a marked increase in larval size occurred prior to the terminal Devonian extinction event. Considering the homogeneity of larval size in older Devonian proetoids, it is interpreted as evidence that the developmental strategy of these trilobites was significantly modified. Though largely speculative, two alternative hypotheses are proposed to explain this modification. Finally, all three ontogenetic sequences show that ocular structures never develop externally in Drevermannia, but also illustrate that the development of optical nerves is not completely lost in this group. This suggests that blindness in the Drevermannia lineage followed a centripetal mode of eye reduction.
Keywords: TRILOBITA; PROETIDAE; ONTOGENY; FAMENNIAN; PALAEOECOLOGY; Палеозой::Девонская::Верхний::Фаменский; Paleozoic::Devonian::Upper::Famennian